A természeti létezők tipológiája Arisztotelésznél. Első rész - Molnár, Gábor (Acta Scientiarum Socialium, 2022)
The first part of the paper (appearing here) examines the typology Aristotle proposes as the extension of the term “things that exist by nature” in Physics B.1 and compares it to passages containing similar typologies in the Aristotelian corpus, most importantly Metaphysics D.8, Z.2, H.1, De Caelo G.1, and Meteorology A.1. The comparative analysis shows that – even though Aristotle introduces the lists in different philosophical contexts and one can find several instances of discord between them – there is a remarkable coherence between his verbal definitions of what exactly the items are the subtypes of. Part Two (appearing in the next issue) will first show that the structuring principles behind the lists can be ordered into a series developed rather consistently according to the same blueprint. After comparing this virtual series with what we can say about the chronological order of Aristotle’s works, the paper will attempt to explain the structural coherence by analysing the interplay between Aristotle’s concepts of nature and of substance and go on to discuss, from this angle, Aristotle’s revisionist treatment of the items on the lists one by one: the elements, inanimate natural objects, living beings and their parts, celestial bodies, and the heaven. Based on the findings, at the end of the paper a cautious attempt is made at an interpretation of the Aristotelian concepts of nature and substance in terms of the sociology of knowledge.
Keywords: Aristotle’s natural philosophy; concept of nature; theory of substance; types of natural substances; revisionist metaphysics